2020
DOI: 10.1002/ejic.202000521
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Phosphate Nanoparticles Produced in Saliva

Abstract: This paper reports the formation of zinc phosphate nanoparticles from the artificial digestion of zinc chloride. Initially, the formation of amorphous primary particles with a mean radius of 1.1 nm is observed, alongside the formation of larger, protein stabilized aggregates. These aggregates, with a radius of gyration of 37 nm, are observed after 5 minutes of exposure to artificial saliva and are shown to be colloidally stable for a minimum time of two weeks. The initially formed primary particles are thought… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…Similarly, Choudhary et al [93] fabricated zinc encapsulated chitosan NPs to promote maize crop yield. In another synthesis method, Saloga et al [75] reported de novo synthesis of ZnPNPs using ZnCl2 and artificial saliva precursor through an artificial digestion process. The small angle X-ray scattering (SAXS) experiment demonstrated the formation of NPs along with larger protein stabilized aggregates within 5 min of digestion and the size of the particle was estimated to be 1.1 nm.…”
Section: Biological Methodsmentioning
confidence: 99%
“…Similarly, Choudhary et al [93] fabricated zinc encapsulated chitosan NPs to promote maize crop yield. In another synthesis method, Saloga et al [75] reported de novo synthesis of ZnPNPs using ZnCl2 and artificial saliva precursor through an artificial digestion process. The small angle X-ray scattering (SAXS) experiment demonstrated the formation of NPs along with larger protein stabilized aggregates within 5 min of digestion and the size of the particle was estimated to be 1.1 nm.…”
Section: Biological Methodsmentioning
confidence: 99%
“…The success of such a holistic approach, as well as the spectrum of its application, can be evaluated from the rich variety of an increasing number of papers to which the MOUSE has already contributed to. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] 10 -2 10 -1 10 0 10 1 10 2 q (nm −1 ) 10 0 q min, Mo q min, Cu q max, Cu q max, Mo Figure 2. A MOUSE project dataset from a ZIF-8 powder sample consisting of ≈ 35 nm particles, measured using two different X-ray sources (yellow: copper, blue: molybdenum).…”
Section: Jinst 16 P06034mentioning
confidence: 99%